Analisis Kebutuhan Bahan Ajar Berbasis Web-Blog untuk Meningkatkan Kemampuan Berpikir Kausalitas pada Siswa SMA 1 Merangin - Maidah, Al; Yefterson, Ridho Bayu (Jurusan Sejarah FIS UNP, 2025)
The background of this study began with the lack of teaching materials used by teachers and students which had an impact on the low causal thinking skills of students in schools. This study aims to develop web-blog-based teaching materials that are appropriate to be used as a source of supporting teaching materials in improving causal thinking in history lessons at SMA N 1 Merangin. The method used in this study is a mixed method with data collection techniques through observation and interviews and reinforced with simple tests on students so that researchers are able to obtain a needs analysis through the development of web-blog-based teaching materials. Based on these results, researchers identified a lack of teaching materials used by teachers and students in the learning process. The problems researchers encounter, then researchers want to develop teaching materials that can help support students. Of the many teaching materials that can support students, researchers use technology. With the use of technology, it will create diverse and interesting learning styles and become a support in improving students' thinking skills. The web-blog-based teaching materials that researchers develop in this study are an opportunity for students to make learning activities more interesting. So that they can improve causal thinking skills in history learning.